Saturated permeability and water retention capacity in biochar-methanotrophs-clay for new landfill cover system - Wenjing Sun; Gaoge Sun; Shuyun Zhang (Biogeotechnics)
A new landfill cover system, biochar-methanotrophs-clay (BMC) cover is recommended for reducing methane emissions at landfills. It also contributes to decreasing soil permeability and improving soil water retention in a long time, due to highly porous structure of biochar and the growth metabolism of methanotrophs. To determine the effects of biochar content, oxidation aging times and methane-filled days on hydraulic properties, a total of 60 groups of experiments were conducted. The saturated hydraulic conductivity (ksat) was obtained by flexible wall permeameter with controllable hydraulic head pressure. The results showed that the ksat of BMC increased with increasing biochar content and oxidation aging times, while decreased with adding methane-filled days. The soil-water characteristic curves (SWCCs) were obtained with soil suction measured by the filter paper method. The results indicated the water retention capacity of MBC reduced with increasing oxidation aging times but increased with adding methane-filled days. Detected by mercury intrusion porosimetry (MIP), fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM), the differences displayed the changes of pore structures and extracellular polymeric substances (EPS). The oxidation aging of biochar increased the volume of pores, resulting in the increased ksat and the decreased water retention capacity. However, the growing of methanotrophs decreased the volume of pores, resulting in the ksat decreased and the water retention capacity increased due to EPS. No matter how many times the oxidation aging process was experienced, the BMC with longer methane-filled days exhibited relatively lower ksat and better water retention capacity. This implied a more stable barrier capacity to reduce water infiltration in the long term. By combing a series of macro and micro experiments, this paper provides theoretical guidance for the application of biochar-methanotroph-clay mixture to landfill covers.